2014
DOI: 10.1093/brain/awu321
|View full text |Cite
|
Sign up to set email alerts
|

A single session of cerebellar theta burst stimulation does not alter writing performance in writer’s cramp

Abstract: Sir, There has been a growing interest in the role of the cerebellum in primary dystonia. Although this role is not yet fully understood (Sadnicka et al., 2012), an elegant paper by Hubsch et al. (2013) in Brain showed that in writer's cramp, a form of task-specific primary hand dystonia, the cerebellum has lost its ability to modulate sensorimotor plasticity of the motor cortex. As part of their study, they used the paired-associative stimulation protocol, a transcranial magnetic stimulation-based interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…On the other hand, a randomized sham-controlled study revealed no benefits after a single session of 1 Hz repetitive TMS over the cerebellum in 10 patients with writer’s cramp. 141 A related study using a similar single-session paradigm showed no changes in the kinematics of abnormal movements for 13 patients with cervical dystonia and 13 with hand dystonia. 142 It remains to be determined whether the different outcomes reflect differences in the dystonia populations studied or other factors in study design such as duration of TMS.…”
Section: Methodsmentioning
confidence: 94%
“…On the other hand, a randomized sham-controlled study revealed no benefits after a single session of 1 Hz repetitive TMS over the cerebellum in 10 patients with writer’s cramp. 141 A related study using a similar single-session paradigm showed no changes in the kinematics of abnormal movements for 13 patients with cervical dystonia and 13 with hand dystonia. 142 It remains to be determined whether the different outcomes reflect differences in the dystonia populations studied or other factors in study design such as duration of TMS.…”
Section: Methodsmentioning
confidence: 94%
“…None of four studies using non-invasive cerebellar stimulation as therapy in focal hand dystonia found any significant clinical effect or a correlation between the neurophysiological parameters and the arm kinematics [218, 219, 255, 256]. This absence of acute clinical effects is not surprising especially after only a single session of cerebellar stimulation [257].…”
Section: Non-invasive Stimulation In Humansmentioning
confidence: 99%
“…One session of cTBS to cerebellum failed to improve the writing performances of writer’s cramp patients [158]. One session of anodal tDCS was reported to improve the kinematics of handwriting (reduced mean stroke frequency and average pen pressure and increased writing speed) in 8 people with focal hand dystonia [56] while there was no effect on the WCRS and investigator or self-rated assessment of handwriting speed [154].…”
Section: Noninvasive (Transcranial Magnetic (Tms) and Transcranial DImentioning
confidence: 99%